“It’s Boring, If I Listen Too Long I’ll Get Sleepy” A Phenomenological Study to Design Educational Media for Pregnancy Women's Class - Salsabila, Salma; Urrahman, Dhiya; Baiquni, Fahmi; Sulistyowati, Endang Tri (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Prenatal class are conducted to enhance the knowledge of pregnant mothers regarding their pregnancy comprehensively and systematically, and can be carried out continuously. This activity will be effective when pregnant mothers are able to comprehend and implement the health information provided by healthcare personnel. This research aims to examine and design appropriate health promotion media for groups of pregnant women in the effort to participate in prenatal classes in Sukoharjo, Wonosobo. This research is qualitative with a phenomenological approach, involving 18 participants. Data were obtained through Focus Group Discussions and in-depth interviews. The research results indicate that the suitable health promotion media for groups of pregnant women is an animated video with the message of Exclusive Breastfeeding, using the Indonesian language. The desired appearance includes bright colors and comprehensive message content, with the delivery method distributed through group chats and regularly explained repeatedly.